Phenol Adsorption from Simulated Wastewater Using Activated Spent Tea Leaves - Raheem, Noora A.; Majeed, Najwa S.; Al Timimi, Zahraa (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
The removal of phenol from wastewater has become a significant environmental concern because of its toxicity, even at low concentrations. This research focuses on the removal of phenol using spent tea leaves (STLs) as an adsorbent. SEM and FTIR tests were used to evaluate the surface characterization of the STLs. The effect of the parameters such as initial phenol concentration (20 - 80 mg. L-1), pH (3 - 12), temperature (25 - 55 °C), contact period (30-330 min), and dose (0.25 - 2.5) on the removal of phenol was studied. The highest removal of phenol of 82% was obtained at 20 mg. L-1 of initial phenol concentration, 4 h of the contact period, pH of 3, adsorbent dose of 2 g, and temperature of 55 °C. The results of the kinetic study fitted the pseudo-second-order model. The obtained data for phenol adsorption isotherm fitted to the Langmuir, Freundlich, and Temkin models. The Temkin isotherm model presented the best fitting with phenol adsorption isotherm experimental data based on the correlation coefficients. According to the findings, the STLs can effectively remove phenol from wastewater.